Analysis And Recommendations For The Vietnam’s Legal Framework On Cybercrime - Khoat, Nguyen Van (Jurnal Cita Hukum, 2025)
Cybercrime has emerged as a complex global threat that continuously evolves, posing challenges not only to states and law enforcement but also legal experts, computer professionals, and researchers. Despite its growing significance, there is no universally accepted definition of cybercrime, further complicating legislative and enforcement efforts. Vietnam, with one of the highest internet penetration rates in the world—over 80% of its population or approximately 80 million users, is particularly vulnerable to cybercrime. Recognising this risk, Vietnam enacted the Cybersecurity Law in 2018 and addressed cybercrime provisions in the amended Criminal Code of 2015 (revised in 2017). This article aims to analyse the effectiveness of Vietnam’s legal framework on cybercrime and offer constructive recommendations for improvement. Utilising a qualitative research method through a literature-based and legal approach, the study conducts comparative legal analysis by examining relevant regulations and policies in Vietnam, Singapore, and the United States. The research reveals that although Vietnam has made significant strides in legislating cyber-related issues, its Cybersecurity Law 2018 places disproportionate emphasis on state control and lacks provisions that adequately protect individual rights or facilitate inter-agency cooperation. In contrast, countries like the U.S. emphasise robust information-sharing mechanisms among cybercrime investigation bodies, which enhances enforcement efficiency. The article concludes that Vietnam’s legal framework would benefit from reforms that better balance national security and individual freedoms while fostering inter-agency collaboration and alignment with international best practices in cybersecurity governance.